Intraoperative nerve monitoring during thyroidectomy: evaluation of signal loss, prognostic value and surgical strategy - Gür, EO (Ann R Coll Surg Engl, 2019)
INTRODUCTION: Intraoperative neural monitoring of the recurrent laryngeal nerve has been widely used to avoid nerve injury during thyroidectomy. We discuss the results of the change in surgical strategy after unilateral signal loss surgeries using intermittent intraoperative neural monitoring in a high-volume referral centre. MATERIALS AND METHODS: Details of consecutive patients who underwent thyroidectomy with intermittent intraoperative neural monitoring between January 2014 and December 2017 were prospectively recorded and retrospectively reviewed. Loss of signal was defined as recurrent laryngeal nerve amplitude level lower than 100 μV during surgery. The rate of loss of signal and change in surgical strategy during the operation were evaluated. RESULTS: Loss of signal was detected in 25 (5.4%) of 456 patients for whom intermittent intraoperative neural monitoring was performed. Four patients had anatomic nerve disruption and surgery was completed by an experienced endocrine surgeon making use of intraoperative neural monitoring with continuous vagal stimulation. Staged thyroidectomy was performed on 16 patients with unilateral loss of signal in whom the nerves were intact visually. Postoperative vocal cord paralysis was encountered in 18 of 21 (85.7%) patients with loss of signal, and 16 of 18 (88.8%) were improved during the follow-up period. Patients’ voices were subjectively normal to the surgeon postoperatively in 9 of 21 (42.8%) patients who were found to have loss of signal with intact nerves. CONCLUSIONS: Intraoperative neural monitoring can be used safely in thyroid surgery to avoid recurrent laryngeal nerve injury. It enables the surgeon to diagnose recurrent laryngeal nerve injury intraoperatively to estimate the postoperative nerve function and to modify the surgical strategy to avoid bilateral vocal cord paralysis.